PENGARUH PARTISIPASI ANGGARAN, PENEKANAN ANGGARAN, DAN KOMITMEN ORGANISASI TERHADAP SENJANGAN ANGGARAN PADA SUKU DINAS PEMERINTAHAN DI DKI JAKARTA - Putra, I Gede Eka Dharma; Mintoyuwono, Danang (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
The study aims to determine the influence of budgetary participation, budget emphasis and organisation commitment on budgetary slcak. Respondents were studied were departement chief, head of subsection, and section chief in departements at west jakarta, south jakarta, north jakarta, central jakarta, and east jakarta . Data collection techniques in this research using primary data by distributing questionnaires to 211 respondents. Technique data processing was performed using SPSS 21 and assisted by using microsoft office 2010. The variables studied consisted of budgetary participation, budget emphasis, organisation commitment and budgetary slack. The analysis used to test this research is multiple linear regression test. Partial results of the study showed absence of budgetary participation significant effect on budgetary slack, the absence of budget emphasis on budgetary slack, and absence of organisation commitment on budgetary slack. From the results of simultaneous studies showed a significant effect between the variables of budgetary participation, budget emphasis, organisation commitment on budgetary slack.